Online Peer Counseling for Unjani’s College Students in the Society era 5.0 - Pratiwi, Endah Andriani (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
Students as teenagers who will enter early adulthood are faced with various problems, demands and challenges, especially in the Era of Society 5.0. Students find it easier to share their problems with friends than parents, lecturers or others. Here, the role of Peer Counseling becomes important to help students for maintain their mental health. With the Covid-19 Pandemic period and also increasing technological developments, Peer Counseling Online can help students to receive counseling services. The Peer Counseling Online was given briefing and also training implementation of counseling, especially Peer Counseling Online and Psychological First Aid. Using technology media, counseling activities can be done anywhere. The counselees themselves come from various faculties at UNJANI and the most problems experienced by counselees are anxiety. The results of the study proved that counselees felt helped by the existence of Peer Counseling Online services and most felt that they did not need to continue consulting with professionals or Psychology because they felt helped by the existence of Peer Counseling Online.